Balancing immune responses: regulatory cells in eosinophilic gastrointestinal disorders - Kheshtchin, Nassim; Kanannejad, Zahra; Ghahramani, Zahra; Esmaeilzadeh, Hossein; Sepahi, Najmeh (Frontiers in Immunology, 2024)
Eosinophilic gastrointestinal disorders (EGIDs) are a group of conditions characterized by an abnormal accumulation of eosinophils in the gastrointestinal tract, leading to inflammation and tissue damage. Regulatory cells are a subset of immune cells that are crucial in maintaining the balance of the immune system and preventing the occurrence of autoimmune diseases. In EGIDs, regulatory cells are believed to play a key role in controlling the immune response and overseeing the growth and activation of eosinophils in the gastrointestinal tract. There is evidence indicating that regulatory T cells (Tregs) and regulatory eosinophils may play a role in suppressing the inflammatory response in EGIDs. Regulatory eosinophils are a subgroup of eosinophils that possess an anti-inflammatory role. Recent studies have shown that enhancing the number or effectiveness of regulatory eosinophils can reduce the severity of EGIDs. Regulatory eosinophils dampen inflammation through their regulatory mediators, such as galectin-10 and growth factor beta (TGF-β), which promote Treg expansion and inhibit effector T cell function. Further research on regulatory cells in EGIDs may have significant implications for the advancement of novel therapies for these uncommon and intricate disorders. The aim of this review is to provide complete view of the immune responses connected to EGIDs, examine the regulatory cells that control these responses, and evaluate their potential as therapeutic targets for EGID treatment.